Knowledge of Basic Life Support among Final Year Dental Students of BPKIHS - Yadav, Anjani Kumar; Rajesh Jaisani, Mehul; Dongol, Ashok; Acharya, Pradeep (Birat Journal of Health Sciences, 2021)
Introduction: The chance of survival of a victim after cardiac arrest/foreign-body airway obstruction is doubled by early institution of Basic Life Support (BLS). Besides medical doctors, dental doctors might also encounter the patients in emergency situation requiring BLS, especially during peripheral district teaching hospital posting in internship.Objectives: The objective of this study was to assess the level of knowledge about BLS among final year dental students of BPKIHS.Methodology: In this cross-sectional study, structured questionnaires were distributed to BDS final year students (purposive sampling, sample size=53). Each question responded correctly was awarded as point +1 and total points were calculated by adding all the correct answers. The collected data were entered in Microsoft excel 2010 and descriptive analysis was done by SPSS 16.Results: Out of 53 questionnaires distributed, 49 were responded and returned (response rate= 92.45%). Twenty participants were male and twenty-nine were female. Four participants had taken BLS training in the past. Only twenty participants scored ≥ 50% and none of the participant scored ≥75%. Only one question was responded correctly by 100% participants. Ten questions were responded correctly by ≥50% participants. Although 65.3% participants were aware about high quality CPR, only 49% knew the exact location of chest compression. The chest compression to ventilation ratio for each of single rescuer and two rescuers was known by 20 participants (40.8%) and 28 participants (57.1%) respectively.Conclusion: Knowledge of  BLS is poor among BDS final year students.